Genomic Characterization of Severe Acute Respiratory Syndrome Corona Virus-2 (Sars-Cov-2) Strains Circulating in Chennai (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2024)
COVID-19 cases began from January 30, 2020, and continued transmission has ensued in multiple states including Tamil Nadu. During the epidemic, the SARS CoV-2 genome has accumulated several mutations. The evolution of viral variants has significant implications for epidemiology, diagnosis, and management, as well as the emergence of re-infection. In this study, we undertook Whole Genome Sequencing (WGS) of SARS CoV-2 genomes collected from SARS CoV-2 infected persons at two time points one year apart, May 2020 and April/May 2021, from one of the metropolitan cities of India. RNA was extracted from oropharyngeal and nasopharyngeal swab specimens collected from 85 COVID-19 infected individuals with a CT value of less than 30. WGS of SARS CoV-2 was performed using Oxford Nanopore Technology (ONT).A striking change was noticed in the major circulating strains of SARS-CoV-2 from May 2020 (B.1 and B.1.1.1) to May 2021 (B.1.617.1 and B1.1.7). Our findings reveal a clear shift in the distribution of sub-lineages during the last year in the local population, with the newly identified double mutant/variants of concern overtaking the local epidemic. We noticed that infection with the newly emerged mutant strains was more common in the younger age group (18-44 years) as compared to older individuals (>45 Years).We recommend continuous genomic surveillance to identify the emergence of newer strains in the city and detect early warning signs for an upsurge in COVID-19 cases due to new variants. Under the given circumstances, sustained efforts to strengthen enforcement of physical distancing, use of masks and sanitization to contain virus transmission, besides vaccination of younger individuals is advisable